Implementation and Utilization of the Jamsostek Mobile (JMO) Application: The Perspective of Medan BPJS Employees and Participants - Ujung, Natanail Valentinus Karo; Putri, Rafika Aprila; Asyadda, Tabina; Syahputra, Muhammad Bagas Dwi (MSJ : Majority Science Journal, 2026)
This study examines the implementation and utilization of the Jamsostek Mobile (JMO) application at the BPJS Ketenagakerjaan Medan branch from two main perspectives: employees as service providers and participants as application users. The study employs a mixed-method approach involving in-depth interviews with employees and quantitative surveys of participants to obtain a comprehensive overview of this digital service's effectiveness. The results indicate that JMO has successfully increased operational efficiency by reducing queues and administrative burdens, while providing convenience and speed of service for participants. The role of employees as educators is crucial in overcoming users' digital literacy barriers. However, a divergence in perception emerged between employees, who highlighted participants' readiness, and participants, who revealed technical application constraints. Participant satisfaction levels are notably high with a 92% recommendation rate, while employees proposed feature enhancements for optimization. These findings contribute significantly to the evaluation and development of digital social security services in Indonesia, offering integrative insights for strengthening public technology implementation.